Design and Implementation of Medical Ultrasound Remote Control Software Based on Sensor Design - Deng, Shuhao; Jiang, Quan; Zhang, Yingchun; Lu, Xin; Shi, Xiurong; Zhang, Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
With the development of medical technology, medical ultrasound technology is widely used in the diagnosis of human diseases. It has become an indispensable diagnostic method in modern clinical medicine by detecting the internal physiology or tissue structure of the human body by ultrasound and then discovering diseases. Based on this, this paper designs a medical ultrasonic remote control software based on sensor design. The system software communicates with the stimulator through the Bluetooth port of the mobile phone and can send the parameter information input by the mobile phone to the field-programmable gate array of the stimulator for compilation. The upper computer control interface with a remote communication function is written by Lab VIEW software. A socket is used to establish inter-network process connection, and medical ultrasonic equipment simulates hardware key input according to the received control instructions so as to achieve the purpose of remote control. Experiments show that, compared with other systems, the infrared human body temperature measurement system with the functions of environmental temperature compensation and distance compensation can effectively reduce the influence of environmental temperature, distance, and other factors and has the advantages of non-contact, low power consumption, fast response speed, high sensitivity, and high accuracy, which is suitable for rapid and accurate human body temperature measurement in crowded places with large traffic.